2008
DOI: 10.1017/s1352465808004906
|View full text |Cite
|
Sign up to set email alerts
|

CBT for People with Intellectual Disabilities: Emerging Evidence, Cognitive Ability and IQ Effects

Abstract: http://dx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(123 citation statements)
references
References 44 publications
2
117
1
3
Order By: Relevance
“…Taylor et al (2008) reviewed the evidence regarding the impact of full scale IQ and verbal IQ on therapy outcomes, reporting that while some studies reported better outcomes for clients with a higher verbal IQ (Rose, Loftus, Flint, & Carey, 2005;Willner, Jones, Tams, & Green, 2002), others reported greater improvements from pre-intervention to follow-up for clients with lower full scale IQ scores (Taylor, Novaco, Gillmer, Robertson, & Thorne, 2005). This discrepancy could be associated with mode of delivery, individual versus group-based treatments, and intensity or frequency of sessions (Taylor et al, 2008). Meta-analytic evidence supports the first assumption, with both Prout and Nowak-Drabik (2003) and later Vereenooghe and Langdon (2013) affirming greater therapy efficacy for individual rather than group therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al (2008) reviewed the evidence regarding the impact of full scale IQ and verbal IQ on therapy outcomes, reporting that while some studies reported better outcomes for clients with a higher verbal IQ (Rose, Loftus, Flint, & Carey, 2005;Willner, Jones, Tams, & Green, 2002), others reported greater improvements from pre-intervention to follow-up for clients with lower full scale IQ scores (Taylor, Novaco, Gillmer, Robertson, & Thorne, 2005). This discrepancy could be associated with mode of delivery, individual versus group-based treatments, and intensity or frequency of sessions (Taylor et al, 2008). Meta-analytic evidence supports the first assumption, with both Prout and Nowak-Drabik (2003) and later Vereenooghe and Langdon (2013) affirming greater therapy efficacy for individual rather than group therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al [43] state that MBCT enhances the cognitive skills which have inverse correlation with dysfunctional attitudes and as a result reduces such attitudes. According to Michalczuk et al [44], all patients especially those afflicted with refractory diseases have many dysfunctional attitudes and destructive thought patterns.…”
Section: Discussionmentioning
confidence: 99%
“…According to Michalczuk et al [44], all patients especially those afflicted with refractory diseases have many dysfunctional attitudes and destructive thought patterns. During a MBCT course, the patient learns how to identify destructive or annoying thought patterns which have negative effects on his behaviors and begins to understand their effects [43]. Dysfunctional attitudes are no exception to this and they can be corrected during this course.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence that indicates that CBT can be effectively CBT for co-morbid ID and Hoarding 6 adapted to treat emotional disorders including anxiety and depression in people with ID (Taylor, Lindsay & Willner, 2008) and the current study chose to test the effectiveness of CBT based on this evidence. The current study was novel and innovative in attempting to index the safety, effectiveness and durability of CBT for hoarding for the first time in an ID context.…”
Section: Introductionmentioning
confidence: 99%